The Occupational Medicine Surgery in the Health and Safety Units since the National Health Service Institution: Continuity of Mission in a modified Social and Epidemiological Context - Capacci, Fabio; Goglia, Gaetano; Grillo, Annalisa; Sallese, Domenico (La Medicina del Lavoro, 2018)
Aims and Tasks provided by the Health Reform Act in 1978 and entrusted to the Health and Safety local Units are still in force. Their validity is confirmed and the change in their organization, due to a variation of the social context, as well as the evolution of clinical and epidemiological profile of occupational diseases are analysed. In particular the need of an improved diagnostic route, an accurate estimate of past exposures reconstruction and the exposure-risk correlation are stressed. Occupational physicians are nowadays facing with delicate judgements of working fitness given the ageing of the working population. In these contexts Public Health Services should be a solid point of reference for occupational physicians, workers and companies. The experience of the Health and Safety Unit in Florence, adjusted to the new challenges in occupational healthcare activity. is described. Some indicators like number of examinations, occupational diseases diagnosed and relationships with other specialized physicians and prevention campaigns encourage to carry on with the mission.